Culture du risque cyclonique et résilience individuelle en Guadeloupe et à Saint-Martin - Fanny Benitez; Magali Reghezza-Zitt; Nancy Meschinet de Richemond (EchoGéo)
This paper addresses the notion of “risk culture”, used in the French natural disaster prevention and crisis management field. Following the 2017 cyclonic season, various managers underlined the risk culture of the « French Carribean populations » to explain their resilience. By combining inhabitants testimonies and crisis managers interviews, we show that individuals are aware of the cyclonic risk and know the safeguarding measures, but that the risk is underestimated and the preparation is uneven. We return to the necessary contextualization of a "culture of risk" at the individual level and discuss its role in people's resilience.